THE EFFORT OF IMPROVING THE INTERVIEW ABILITY THROUGH THE IMPLEMENTATION OF ROLE PLAYING LEARNING MODEL FOR THE GRADE VIII A STUDENTS OF SMP NEGERI 1 MANDREHE ACADEMIC YEAR 2018/2019 - Waruwu, Juni Artati (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
This research was motivated by the lack of students' ability in interviewing. The purpose of this paper is to describe the process of implementing the Role Playing learning model in interviewing material, to describe the improvement of students' ability in interviewing through the application of the Role Playing learning model. The writing method used is Classroom Action Writing (CAW). Based on the results of writing, the average student learning outcomes in the first cycle was 63.40, while the average student learning outcomes in the second cycle were 74.80. Based on the results of the research findings, it can be concluded that the application of the Role Playing learning model is because it is able to make students prioritize how to master learning materials through developing students 'imagination and appreciation so that there is an increase in students' interviewing abilities. Researcher's suggestion is for Indonesian language subject teachers, they should choose and apply the Role Playing learning model because students are able to prioritize how to master the learning materials so that interviewing skills and student learning outcomes can be improved, and for further researchers they should use the Role Playing learning model because students able to prioritize how to master the learning materials so that the desired results can be achieved.